Hyperthermia in a Patient with Relapse Malaria: A Case Report - Mujahidah, Shafira Aulia; Sari, Eka Afrima; Pebrianti, Sandra (Nursing Case Insight Journal, 2025)
Malaria is an infectious disease that caused by Plasmodium infection in red blood cells. The main clinical manifestations that appear in malaria are fever with shivering, shaking, and sweating and weakness. This condition can cause severe hyperthermia, which is at risk of causing brain damage, seizures, or delirium. This study aims to see the characteristics of fever and implementation in patients with malaria relapse. A 41-year-old man with a history of malaria four months ago. During the first malaria, the patient experienced fever to shivering and sweating as well as muscle pain and fatigue every morning. In malaria relapse, complaints of fever and chills every morning were exacerbated by complaints of dizziness as if being hit and weakness. Laboratory examination results found Plasmodium vivax gametocyte and schizont stages. The patient received paracetamol, cefixime, dexamethasone, and DHP Frimal therapy as well as Tepid Water Sponge therapy. After three days of treatment with a combination of pharmacological therapy and tepid water sponge, there was a decrease in temperature from 38.4°C with warm extremities, sweating, headache and shivering to 37.8°C on the second day and 36.7°C on the third day with warm extremities and no shivering, no headache and more fit. The administration of a combination of pharmacological and non-pharmacological tepid water sponge therapy in patients with malaria relapse was able to reduce hyperthermia. Further researchers are expected to be able to examine more widely the effectiveness of actions to reduce hyperthermia in adult patients with malaria.